Peran Organisasi Pekka Dalam Mengembangkan Modal Sosial Keluarga Anggota Organisasi Pekka Di Kabupaten Situbondo - Bariq, Jamilatul; Utami, Diyah (Paradigma, 2026)
Abstract This study aims to analyze the role of Pekka organizations in developing the social capital of Pekka organization members. Rural women often experience gender inequality and the existence of unequal roles between women and men so that village women build women’s empowerment. The study used a qualitative approach with a purposive sampling technique. The analysis was conducted using Pierre Bourdieu’s social capital ethnomethodology. The results of the study indicate that the social capital of empowering village women has a positive impact on the development and improvement of women’s capacity to build the village economy through social networks, trust and access to social resources of village women. This study provides the conclusion that the Pekka Organization plays an important role as a forum for empowering women heads of families which not only has an impact on improving economic welfare and strengthening social and psychological capacity. Pekka is able to create a safe and productive space for women to build social capital, increase income, obtain legal support and strengthen their position in the family and community. Keywords: Ethnomethodology, Pekka Organization, Women, Community Empowerment. Abstrak Penelitian ini bertujuan untuk menganalisis peran organisasi Pekka dalam mengembangkan modal sosial anggota organisasi Pekka. Perempuan desa sering kali mengalami ketidaksetaraan gender dan adanya ketimpangan peran anatar perempuan dan laki – laki sehingga perempuan desa membangun pemberdayaan perempuan. Penelitian menggunakan pendekatan kualitatif dengan teknik purposive sampling. Analisis dilakukan menggunakan Etnometodologi modal sosial Piere Bourdie.Hasil penelitian menunjukkan bahwa modal sosial pemberdayaan perempuan desa memberikan dampak positif dalam pengembangan dan peningkatan kapasitas perempuan untuk membangun perekonomian desa melalui jaringan sosial, kepercayaan dan akses sumber daya sosial perempuan desa. Penelitian ini memberikan kesimpulan bahwa Organisasi Pekka berperan penting sebagai wadah pemberdayaan perempuan kepala keluarga yang tidak hanya berdampak pada peningkatan kesejahteraan ekonomi dan penguatan kapasitas sosial dan psikologis. Pekka mampu membangun ruang aman dan produktif bagi perempuan untuk membangun modal sosial,meningkatkan pendapatan,memperoleh dukungan hukum serta memperkuat posisi mereka dalam keluarga dan masyarakat. Kata Kunci: Etnometodologi, Organisasi Pekka, Perempuan, Pemberdayaan Masyarakat